Influence of force-vector and force application plyometric training in young elite basketball players - Gonzalo-Skok, O.; Sánchez-Sabaté, J.; Izquierdo-Lupón, L.; Saez de Villarreal, E. (European Journal of Sport Science, 2019)
Plyometric training composed by unilateral exercises with horizontal jumping direction seems to be an effective way to improve physical performance in athletes. The present study aimed to compare the influence of a combined jumping direction and force application (horizontal-unilateral vs. vertical-bilateral) plyometric training on linear sprinting, jumping, change of direction (COD) and dynamic balance in young elite basketball players. Twenty young (U-13 to U-14) male basketball players (age: 13.2 ± 0.7 years, body mass: 59.5 ± 12.7 kg, height: 172.9 ± 7.9 cm) were randomly assigned either to a unilateral-horizontal (UH, n= 10) or bilateral-vertical (BV, n= 10) plyometric group, twice a week for 6-wk. Both groups performed between 60 and 100 jumps/session. UH executed all jumps unilaterally with horizontal direction, while jumps in the BV were bilaterally with vertical direction. Performance was assessed by a linear sprinting test, vertical and horizontal jumping tests, COD tests (V-cut and 5+5 m with a 180°COD test), an ankle dorsiflexion test and dynamic balance tests (anterior and postero-lateral directions). Within-group differences showed substantial improvements (Effect size (ES):0.31 - 1.01) in unilateral vertical and horizontal jumping, V-cut test and postero-lateral direction with right leg after both training interventions. Furthermore, UH group also substantially improved (ES:0.33 - 0.78) all sprinting times and postero-lateral direction with left leg, while BV enhanced anterior direction with left leg (ES:0.25). Between-group analyses showed substantially greater improvements (ES:0.33) in 10-m and V-cut test in UH than in BV. The likely beneficial effect (small ES) achieved in sprinting abilities suggests the combination of unilateral-horizontal jumps to improve such abilities.